The Correlation Between Students Healthy Lifestyle and The Academic Achievement One the Students STIKes Medika Nurul Islam - Inayati, Rahmi; Mardhiah, Ainal; Bashir, Asri; Ikhsan, Muhammad (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Student academic achievement is very much determined by the lifestyle they carry out during the lecture process. Students who have a healthy lifestyle will live their lives by paying attention to factors that affect health, such as avoiding addictive items, paying attention to a balanced healthy diet, a balanced healthy menu and regular physical activity. This will cause their health level to be better. Research Objectives to determine the relationship between a healthy lifestyle and academic achievement of STIKes Medika Nurul Islam students. Research methodology: this research method is correlation analytic with cross sectional design approach. The population in this study were all level III students at STIKes Medika Nurul Islam. Sampling with total sampling of 98 respondents. The results showed that the majority of healthy lifestyle is good, namely (70.7%). Most of the satisfactory academic achievement is (57.6%). The results of statistical tests with Spearman rank obtained p value 0.000 <0.05. Conclusion: there is a relationship between a healthy lifestyle and academic achievement in students. Suggestion: it is hoped that students, especially nursing students, should know more about the importance of a healthy lifestyle, so that students stay healthy in following the learning process so that they can achieve good academic achievement.